Research on the Innovation of State owned Enterprise Political Work Based on Corporate Culture - Zhang, Xuefang (Journal of Theory and Practice of Social Science, 2023)
State owned enterprises play a crucial role in promoting the development of the national economy and improving the level of modernization construction in China. In state-owned enterprises, political work and the construction of corporate culture are essential basic tasks that are needed in daily life. So in order to ensure the continuous development of state-owned enterprises in a fiercely competitive environment, it is necessary to combine corporate culture with political work to jointly achieve innovative development.